2009
DOI: 10.1017/s0266462309990201
|View full text |Cite
|
Sign up to set email alerts
|

Home telehealth for chronic disease management: A systematic review and an analysis of economic evaluations

Abstract: Current evidence suggests that home telehealth has the potential to reduce costs, but its impact from a societal perspective remains uncertain until higher quality studies become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 31 publications
1
101
0
3
Order By: Relevance
“…One review found that a societal perspective on costs has not yet been developed for home telehealth [71] and another highlighted the need to consider not only costs to health services of interventions, but also costs to service users and their social networks [72].…”
Section: Economic Analysismentioning
confidence: 99%
“…One review found that a societal perspective on costs has not yet been developed for home telehealth [71] and another highlighted the need to consider not only costs to health services of interventions, but also costs to service users and their social networks [72].…”
Section: Economic Analysismentioning
confidence: 99%
“…Linton proposed studies to clarify how patients should be selected for treatment, and of the role of CCBT compared with other treatments [73]. Polisena et al argued that controlled studies of higher quality were required in home telehealth for diabetes management in order to give more precise insights into clinical effectiveness [74][75]. They added that studies should also include more diverse diabetes populations to increase the external validity of the outcomes, and examine the impact of various clinical approaches to determine optimal telehealth use.…”
Section: Combining Summative and Formative Assessmentsmentioning
confidence: 99%
“…A second study (Polinesa et al, 2009) also reviewed the literature on the cost-effectiveness of home telehealth for chronic disease. Their review included economic assessments such as cost minimization analyses, cost-effectiveness analyses, cost utility analyses and cost benefit analyses.…”
Section: Economic Backgroundmentioning
confidence: 99%